2005
DOI: 10.1590/s0100-83582005000200019
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de chama para controle de plantas daninhas emersas em ambiente aquático

Abstract: Dois estudos foram conduzidos com o objetivo de avaliar os efeitos da aplicação de chama no controle de Eichhornia crassipes, Brachiaria subquadripara, Pistia stratiotes e Salvinia auriculata. No primeiro estudo foram utilizadas diferentes doses de chama, representadas pela quantidade de gás consumida durante a aplicação, e, no segundo, usaramse duas aplicações de chama em intervalo de 14 dias, uma aplicação seqüencial (intervalo de sete dias) e aplicação única. As diferentes doses, tanto no primeiro quanto no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…This flamethrower time reduced the fresh matter weight to 41.09 g m -2 , the dry matter weight to 6.72 g m -2 , and the infestation percentage to 9.49%, in relation to the absence of flamethrower; these values correspond to a reduction of 94.47, 92.02 and 86.69%, respectively. Marchi et al (2005), evaluating the use of a flamethrower to control weeds on an aquatic environment on soil-filled vases, observed that the highest percentage reductions of dry matter weight were obtained for Brachiaria subquadripara, with doses of 2,226, 1,113 and 556 kg ha -1 of LPG, offering reductions of 77.6, 74.2 and 78.3%, respectively. This result was different than the one observed on this paper, in which, with a dosage of 27.7 kg ha -1 of LPG, equivalent to 10 s m -2 of application of the flamethrower, a reduction of 92% on the dry matter weight of weeds could be obtained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This flamethrower time reduced the fresh matter weight to 41.09 g m -2 , the dry matter weight to 6.72 g m -2 , and the infestation percentage to 9.49%, in relation to the absence of flamethrower; these values correspond to a reduction of 94.47, 92.02 and 86.69%, respectively. Marchi et al (2005), evaluating the use of a flamethrower to control weeds on an aquatic environment on soil-filled vases, observed that the highest percentage reductions of dry matter weight were obtained for Brachiaria subquadripara, with doses of 2,226, 1,113 and 556 kg ha -1 of LPG, offering reductions of 77.6, 74.2 and 78.3%, respectively. This result was different than the one observed on this paper, in which, with a dosage of 27.7 kg ha -1 of LPG, equivalent to 10 s m -2 of application of the flamethrower, a reduction of 92% on the dry matter weight of weeds could be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Flamethrower application time in weed control Marchi et al (2005), assessing the use of flamethrowers to control weeds on an aquatic environment, when planted on soil vases, observed that all sequential applications offered a reduction of over 90% in the production of dry biomass of E. crassipes and B. subquadripara, concluding that the physical control by applying the flame is an alternative to manage weeds in aquatic environments.…”
Section: Introductionmentioning
confidence: 99%
“…Já as ceifadeiras mecânicas são máquinas flutuantes de grande porte que além de cortar recolhem as macrófitas aquáticas (Figura 8). Há também referência ao uso do fogo por meio de aplicação de chama diretamente sobre as macrófitas aquáticas (MARCHI et al, 2005b).…”
Section: Procedimentos De Controleunclassified
“…Novas tecnologias relacionadas ao manejo de plantas espontâneas vendo sendo desenvolvidas, no entanto, a grande maioria estão direcionadas ao uso e manejo dos herbicidas, deixando assim uma lacuna a ser preenchida com o desenvolvimento de pesquisas voltadas as formas alternativas de manejo das espécies espontâneas. Nesse foco, há algumas pesquisas sendo desenvolvidas, como com o uso de chamas (fogo) direcionados (MARCHI et al, 2005) e da descarga elétrica (BRIGHENTI e BRIGHENTI, 2009), mas ainda com limitações quantos aos efeitos ambientais e custos.…”
Section: Introductionunclassified